Spinal decompression and radionuclide therapy for an unresectable FGF23 transmitted tumor causing cervical myelopathy: a case report and literature review - Yokoyama, Shin; Shimizu, Hirokazu; Yuno, Akiko; Takenaka, Junki; Wakabayashi, Naoto; Watanabe, Shiro; Kuwahara, Ken; Matsuoka, Masatake; Onodera, Tomohiro; Iwasaki, Norimasa; Iwata, Akira (Frontiers in Oncology, 2026)
BackgroundTumor-induced osteomalacia (TIO) is a rare disorder characterized by hypophosphatemic osteomalacia, mainly caused by benign tumors with excessive secretion of fibroblast growth factor 23 (FGF23) and somatostatin receptor expression. Although complete excision is recommended, reports on treatment strategies for anatomically challenging surgical cases are lacking. We report an unresectable case of FGF23 transmitted tumor in the cervical vertebrae causing myelopathy, which was treated with surgical decompression combined with radionuclide therapy.Case presentationA 52-year-old woman presented to another hospital with complaints of knee pain. After confirming abnormal tracer uptake at the C7 vertebrae using somatostatin receptor scintigraphy and an elevated serum FGF23 level (>800 pg/mL), TIO was diagnosed 7 years after the initial presentation. Gait disturbance occurred 10 years after the initial presentation; therefore, the patient was referred to our department. Magnetic resonance imaging revealed a tumor with spinal cord compression and vertebral artery encasement, making complete resection impossible. Gait disturbance improved after spinal decompression with partial resection of the tumor. Peptide receptor radionuclide therapy targeting somatostatin receptors was initiated 2 years after surgery. Serum phosphate levels normalized, and the tumor size remained stable after the initiation of PRRT. Ambulation was maintained without joint pain recurrence at 3 years after surgery.ConclusionsThe current literature on FGF23 transmitted tumors in the cervical spine includes six cases treated with definitive local therapy. This case suggests an alternative option for unresectable FGF23 transmitted tumor in the vertebrae, causing spinal myelopathy.